THE URBAN PLANNING CONCEPT BASED ON SMART CITY APPROACH - Muhammad Bakri; Anita Ahmad Kasim (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2018)
Smart City comes as a strategy to reduce the problem due to rapid urban growth and urbanization. The concept of Smart City is needed to ensure the conditions of a habitable City in the context of rapidly growing urban population growth. The urgency of this challenge prompted many cities to begin to find smarter ways of managing urban areas. One way to make the concept of the smart city is to make the city an icon that is sustainable and livable. This study aims to provide the necessary information in building and developing a city through the smart city approach. This paper clarifies the meaning of the word